Faktor yang Berhubungan dengan Implementasi Perilaku Hidup Bersih dan Sehat (PHBS) pada Tatanan Rumah Tangga - Orisinal, Orisinal; Fathimi, Fathimi; Rahmi, Cut; Devi, Desriati; Hermansyah, Hermansyah; Zakaria, Radhiah; Hanum, Nisrina (Jurnal Ragam Pengabdian, 2026)
Clean and Healthy Living Behavior (PHBS) is essential to prevent disease and improve community well-being. However, its implementation at the household level remains suboptimal in many rural areas of Indonesia. This study aimed to identify factors associated with PHBS implementation among households in Pantan Kemuning Village in 2025. An analytic study with a cross-sectional design was conducted involving 273 heads of households selected using total sampling. Data were collected through questionnaires and observations and analyzed using chi-square and logistic regression tests. The results showed that education (p=0.012), knowledge (p<0.001), attitude (p=0.012), and the role of health workers (p=0.042) were significantly associated with PHBS implementation. Multivariate analysis revealed that knowledge was the most dominant factor (AOR=3.38; 95% CI: 1.85–6.16). In conclusion, knowledge plays a key role in determining PHBS implementation. Strengthening community health education and enhancing the involvement of health workers are necessary to improve healthy behaviors in rural communities with sanitation and environmental health challenges.